Evidence-based diabetes nutrition therapy recommendations are effective: the key is individualization - Franz MJ; Boucher JL; Evert AB (Diabetes, Metabolic Syndrome and Obesity, 2014)
Marion J Franz,1 Jackie L Boucher,2 Alison B Evert3 1Nutrition Concepts by Franz, Inc., Minneapolis, MN, 2Minneapolis Heart Institute Foundation, Minneapolis, MN, 3Diabetes Care Center, University of Washington Medical Center, Seattle, WA, USA Abstract: Current nutrition therapy recommendations for the prevention and treatment of diabetes are based on a systematic review of evidence and answer important nutrition care questions. First, is diabetes nutrition therapy effective? Clinical trials as well as systematic and Cochrane reviews report a ~1%–2% lowering of hemoglobin A1c values as well as other beneficial outcomes from nutrition therapy interventions, depending on the type and duration of diabetes and level of glycemic control. Clinical trials also provide evidence for the effectiveness of nutrition therapy in the prevention of diabetes. Second, are weight loss interventions important and when are they beneficial? Modest weight loss is important for the prevention of type 2 diabetes and early in the disease process. However, as diabetes progresses, weight loss may or may not result in beneficial glycemic and cardiovascular outcomes. Third, are there ideal percentages of macronutrients and eating patterns that apply to all persons with diabetes? There is no ideal percentage of macronutrients and a variety of eating patterns has been shown to be effective for persons with diabetes. Treatment goals, personal preferences (eg, tradition, culture, religion, health beliefs, economics), and the individual's ability and willingness to make lifestyle changes must all be considered by clinicians and/or educators when counseling and educating individuals with diabetes. A healthy eating pattern emphasizing nutrient-dense foods in appropriate portion sizes, regular physical activity, and support are priorities for all individuals with diabetes. Reduced energy intake for persons with prediabetes or type 2 diabetes as well as matching insulin to planned carbohydrate intake are intervention to be considered. Fourth, is the question of how to implement nutrition therapy interventions in clinical practice. This requires nutrition care strategies. Keywords: diabetes nutrition therapy, macronutrients, eating patterns, weight loss interventions